Ptychophallus costaricensis, a new freshwater crab from Costa Rica - Villalobos, Carlos R. (Revista de Biología Tropical, 1973)
A new freshwater crab of the genus Ptychophallus is described from Costa Rica, based on the morphology of the gonopod. The species lives under rocks in small streams at an altitude of approximately 1,300 m and at a median water temperature of 16 C. twelve specimens were collected at Quebrada Los Tubos and thirty-two at Río Naranjo, Santa María de Dota, both sites in the Province of San José, Distribution is apparently restricted to the southwest of Costa Rica.